The Clinical Anatomy and Imaging Laboratory: Vertical Integration in the Preclerkship Curriculum - Deborah S. Barry; John M. Dent; Mark Hankin; David Moyer; Neeral L. Shah; Anne Tuskey; Victor Soukoulis (Association of American Medical Colleges, 2019)
Introduction As medical schools implement integrated curricula, anatomy education especially has experienced increased pressure to make foundational content clinically relevant. We designed a novel type of integrative anatomy laboratory experience where students could use foundational anatomy concepts in concert with modern imaging/diagnostic techniques to enhance important clinical concepts. Methods We selected a process called Lesson Study to develop the multidisciplinary Clinical Anatomy and Imaging Laboratory (CAIL) in the cardiovascular and gastrointestinal systems. We utilized soft-embalmed cadavers extensively for their highly realistic tissue appearance and texture, which allowed instructors and students to perform a wide array of procedures in case-based scenarios similar to practicing clinicians. We conducted field observations of participating students, focus-group discussions, and knowledge-based exams to examine efficacy of the CAIL. Results Approximately 150 first- and second-year students participated in each of the CAIL activities on an annual basis. Most focus-group participants felt the CAIL was a great learning experience. They commented on how the lab provided relevance to anatomy knowledge and helped integrate prior classroom learning more deeply. Instructors noted that students asked more advanced, clinically relevant questions than in a typical anatomy lab. Knowledge improved significantly after the CAIL, although it is unclear if this translates to summative exams. Discussion The CAIL creates a unique learning experience where students use prior foundational anatomy knowledge in conjunction with modern imaging and diagnostic techniques to reinforce important clinical concepts. We have continued to integrate CAIL experiences into more clinical systems in our medical school curriculum.